Systemic structure of legality as a fundamental principle of legal legitimacy - Kocharyan, Sergey (Bulletin of Yerevan University C: Jurisprudence, 2023)
In the system of the universal principle of legal legitimacy, the components of the structure of legality are: the goal, sub-goals and sub-functions, the internal elements of each subsystem (principles, requirements), the implementation structure (or guarantees) of the latters. The goal of legal legitimacy is the implementation of law in the behavior of participants in public relations. The goal of legality is the positivization of the objective properties and requirements of the law, which turns into a demand presented to the self-creating bodies to posit only the objective properties of the law and adopt normative acts of a legal nature. Accordingly, the function of legality is to create conditions for the formation of legislation corresponding to the objective nature of social relations, the ideas of freedom, justice and humanism. Guarantees of the implementation of legality are a set of measures, tricks, which are designed to ensure the adoption of normative acts of a legal nature and, in necessary cases, their suspension, their invalidation and elimination after they come into force. The principle of legality is the supremacy of law, which in the stages of law formation and law-making turns into two groups of requirements for the content and procedure of law-making.